2010
DOI: 10.3390/ijerph7083235
|View full text |Cite
|
Sign up to set email alerts
|

Aging Risk and Health Care Expenditure in Korea

Abstract: This paper analyzes the impact of population aging on health care expenditures in Korea. Examination of the age-expenditure profile reveals that health care resources are allocated more for the older cohort of population over time, suggesting significant growth of health care expenditures due to population aging. We contend, however, that population aging is considered as a parameter rather than an independent variable to explain rising health care expenditures. This paper shows that population aging is not fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…We find that, with the exception of Mexico, Estonia is the country with the lowest per capita HCE in our sample. For Korea, besides the determinants we consider in this study, some studies have concluded that the introduction of national health insurance is another factor that boosts the HCE growth (see, e.g., Tchoe & Nam, ). In addition, Figures and depict slowly positive growth in Canada, Denmark, and Finland, and moderately positive growth in other 18 countries.…”
Section: Resultsmentioning
confidence: 99%
“…We find that, with the exception of Mexico, Estonia is the country with the lowest per capita HCE in our sample. For Korea, besides the determinants we consider in this study, some studies have concluded that the introduction of national health insurance is another factor that boosts the HCE growth (see, e.g., Tchoe & Nam, ). In addition, Figures and depict slowly positive growth in Canada, Denmark, and Finland, and moderately positive growth in other 18 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, many health indicators in Korea, including access to medical care, have improved dramatically, adding pressure on the health care budget: from 1989 to 2005, the number of physicians and beds available (per 10 000 persons) more than doubled and the number of physician visits and admissions per capita also nearly doubled . Additionally, the rapidly aging population was considered a major challenge to the national health insurance system . In 2006, the elderly aged 65 years and older accounted for only 8.6% of the population, but they were responsible for 25.9% of health insurance expenditure, which was an increase from 17.7% in 2001 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, the rapidly aging population was considered a major challenge to the national health insurance system. 6 In 2006, the elderly aged 65 years and older accounted for only 8.6% of the population, but they were responsible for 25.9% of health insurance expenditure, which was an increase from 17.7% in 2001. 5 The national health insurance system in Korea began to run a significant budget deficit in 1996 that has grown bigger into the following decade.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] While some studies have suggested that rapid growth in the older adult population (defined as ages 65 and above) is a significant cost-driver for healthcare services, through mechanisms such as increased utilisation due to longer lifespan, [1][2][3]6,8,10 some have argued that the ultimate effect on healthcare expenditure is mild. 5,7,9,11,12 In either case, the magnitude and rate of the increases in the demand for healthcare services relating to age-associated medical conditions has left many countries unprepared. [13][14][15][16][17][18] This has placed a significant financial burden on many governments.…”
Section: Introductionmentioning
confidence: 99%